Implementasi Algoritma Cryptography Clasic Dalam Penyandian Pada Aplikasi Chatting Berbasis Client Server - Saputra, Ripo; Jumadi , Juju; Akbar , Abdussalam Al (CV. Generasi Insan Rafflesia, 2023)
Security and confidentiality issues are one of the important aspects of data, messages and information. One technique that can maintain data confidentiality is cryptography. Vigenere Cipher is one of the classic cryptographic algorithms that works by reading words per character, where if the message sent exceeds the length of the key used, the key will be repeated until the message sent gets each key. The system implementation uses Visual Basic 2010 programming language and the method used in this research is waterfall, this application is designed using UML (Unified Modeling Language). The result of this research is a software application that is useful for maintaining the confidentiality of messages with the Vigenere Cipher algorithm method. With this application can be one solution in securing data in the chat process.